Hubungan antara bobot badan induk dan bobot lahir pedet sapi Brahman cross pada jenis kelamin yang berbeda - Khavida Nuril Muslim; Hary Nugroho; Trinil Susilawati (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2013)
The purpose of the study was to determine the correlation between cow weight and birth weight of Brahman Cross calves with different sex. The materials of the study were one hundred Brahman Cross cows which had been purposively selected. The variables of the study were cow body weight, calves birth weight, and sex. Data were analyzed using Pearson Correlation test (Product-Moment), Linear Regression and t Test. The study found that the birth weight diferred significantly (P <0.05) among male and female calves at the first and third parities. Also, there was significant correlation (P <0.05) between cow body weight and calves birth weight at the first parity. However, this cow body weight only influenced 22-25% on birth weight so that the study suggests to considering other factors such as environment and animal feed. Keywords: body weight, birth weight and bovine